Poly(ester urethane) with Varying Polyester Chain Length: Polymorphism and Shape‐Memory Behavior. Issue 23 (11th September 2013) - Bothe, Martin; Emmerling, Franziska; Pretsch, Thorsten
<x xml:space="preserve">Abstract</x> The swelling, viscoelastic, and mechanical behavior of phase‐segregated poly(ester urethane) (PEU) block copolymers, composed of 4, 4′‐methylenediphenyl diisocyanate, 1, 4‐butanediol as a chain extender, and crystallizable poly(1, 4‐butylene adipate) (PBA) with molecular weights between 1330 and 4120 g mol−1, are investigated. Wide‐angle X‐ray scattering (WAXS) is employed to study the overall PEU crystallinity, which increases from 8.6 to 13.6% at higher PBA contents. The existence of two crystalline, polymorphic PBA phases, a thermodynamically stable α phase and a metastable β phase, is confirmed by further WAXS measurements. Calorimetric and thermomechanical investigations give evidence for controllable PBA polymorphic behavior. The crystallization conditions, like the cooling rate, affect the emerging polymorphic mixture, whereas the storage conditions either promote or inhibit the polymorphic (β to α) transition. The introduced concepts represent a new approach for gaining control over programmable thermoresponsiveness, which may be transferable to other shape‐memory polymers with polymorphic switching segments. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>